Correlation of peripheral blood ZO⁃1 and IL⁃38 levels with lung injury degree in patients with acute respiratory distress syndrome - HE Yanxia，XUE Bing，WU Wenjie，CHEN Xing (Zhongguo linchuang yanjiu)
Objective To analyze the changes of zonula occludens⁃1（ZO⁃1）and interleukin⁃38（IL⁃38）levels in peripheral blood of acute respiratory distress syndrome（ARDS）patients with different degrees of lung injury，and their correlations with the degree of lung injury. Methods A total of 105 patients with ARDS admitted to Chuiyangliu Hospital Affiliated with Tsinghua University from April 2020 to April 2023 were selected as the observation group，and 52 non⁃ARDS patients during the same period were included as the control group. The patients in the observation group were classified into mild，moderate and severe subgroups according to the oxygenation index. The levels of ZO⁃1 and IL⁃38 in the peripheral blood of each group were compared. The correlations of ZO⁃1 and IL⁃38 levels with the degree of lung injury and their predictive value for the survival prognosis of ARDS were analyzed. Results The levels of ZO⁃1 and IL⁃38 in the peripheral blood of patients in the observation group were both higher than those in the control group（P<0.05）. The levels of ZO⁃1 and IL⁃38 in peripheral blood of ARDS patients increased in the order of mild，moderate and severe，with statistically significant differences（P<0.05）. The levels of ZO⁃1 and IL⁃38 in the peripheral blood of ARDS patients were negatively correlated with the oxygenation index（r=-0.716，-0.740，P< 0.01），and were positively correlated with the degree of lung injury（r=0.774，0.729，P<0.01）. Among 105 ARDS patients，40 died and 65 survived within 28 days. The receiver operating characteristic（ROC）analysis results showed that the AUC of ZO⁃1 and IL⁃38 in peripheral blood for predicting the prognosis of ARDS patients were 0.769 and 0.785，respectively，with sensitivities of 85.00% and 80.00%，and specificities of 63.08% and 72.31%，respectively. Conclusion The elevated levels of ZO⁃1 and IL⁃38 in peripheral blood of ARDS patients are correlated with the degree of lung injury and have certain prognostic value.